Javanese Swearing Words: an Analysis of Shifting and Changing Referring Connotative Meaning - Eko Heriyanto (Journal of Language and Health, 2020)
Humans need a language a means of their communication. They use language to communicate with others to gain some purposes in their lives. In their interaction, in a certain condition, they use some swear words to express their feelings. This paper aims to describe the form of swearing words and their references in Javanese Language as the study of shifting and changing of meaning. This research used descriptive qualitative method based on the library and field data. The data are classified and analysed qualitatively. The results of this research are swearing words can be classified into different forms. Regarding to their references, the swearing words mainly refer to animals, bad condition, fruits, parts of body, kinship, sexual activity and ghosts. Most of them are going into shifting and changing of meaning. Some categories have the shifting of meaning, and others have the changing one.